2016
DOI: 10.4103/0301-4738.182943
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antibacterial resistance patterns of extended-spectrum beta-lactamase producing Gram-negative bacteria isolated from ocular infections

Abstract: Purpose:Extended-spectrum beta-lactamases (ESBLs) mediated resistance is more prevalent worldwide, especially among Gram-negative bacterial isolates, conferring resistance to the expanded spectrum cephalosporins. As limited data were available on the prevalence of ESBLs in this area, the current study was undertaken to determine the prevalence, antibacterial resistance patterns, and molecular detection and characterization of ESBL encoding resistance genes among ocular Gram-negative bacterial isolates from ocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
0
17
1
Order By: Relevance
“…In addition, 13/227 isolates were identified as bla CTX - M - 55 -positive in just 7 months. This rate far surpasses other ESBLs [ 21 23 ], which demonstrates the rapid dissemination of bla CTX - M - 55 . Notably, all bla CTX - M - 55 -positive isolates were identified as multiple drug-resistant (MDR) bacteria that are strongly resistant to ceftazidime and cefotaxime (MIC > 256 μg/ml).…”
Section: Discussionmentioning
confidence: 87%
“…In addition, 13/227 isolates were identified as bla CTX - M - 55 -positive in just 7 months. This rate far surpasses other ESBLs [ 21 23 ], which demonstrates the rapid dissemination of bla CTX - M - 55 . Notably, all bla CTX - M - 55 -positive isolates were identified as multiple drug-resistant (MDR) bacteria that are strongly resistant to ceftazidime and cefotaxime (MIC > 256 μg/ml).…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, since systemic antibiotics are still used to treat chronic ocular infections, in such usage, CLSI breakpoints are appropriate. In fact, systemic use of antibiotics may be the key cause of resistance in all isolates, regardless of the source of infection [ 33 , 34 ]. However, the uncertainty of the role of topical antibiotics is still apparent and therefore requires further attention in order to fully delineate their role.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported the prevalence of beta‐lactam resistance genes in ocular clinical isolates of P. aeruginosa , and this ranges from seven per cent to more than 75 per cent . TEM, SHV, OX, and CTX‐M have been found in the chromosome of an ocular P. aeruginosa . In addition, Murugan et al found integration of TEM‐1B, PAO, OXA‐50 and VIM‐2 in the chromosome of multidrug‐resistant P. aeruginosa strain from a keratitis patient .…”
Section: Beta‐lactam Resistancementioning
confidence: 99%